Um estudo sobre as possíveis causas do cancelamento de registro das empresas nacionais de auditoria independente na Comissão de Valores Imobiliários CVM - Uchida, Inácio Mitsuo (2010)
This study seeks to answer the following question problem: what makes independent auditing companies cancel the registration with the CVM? It seeks to present a contribution to understanding the possible causes of the cancellation of auditors registration, considering the quantitative data of auditors canceled, researching the environment of accounting and auditing in Brazil, and the work of independent auditors in major markets in the independent audit Brazil, in other words, business- Traded and Financial Institutions for the period 1998 to 2009. The research method used was the multiple case study, with a selection of three national companies to independent audit that cleared the record in the Securities and Exchange Commission. The objectives of the research are: collecting data for statistical analysis with the competent organs; review the literature on the activities of the auditor and the independent auditing firms; researching the legal and technical requirements issued by standard setters and supervisory institutions of the profession. Based on analysis of the results, it intends the aspiration of reaching the conclusion that the selected companies cancel the registration, why not have a cost/benefits, to meet the requirements of regulating agencies, standard setters and the risks inherent in the activity independent audit